Spousal Support and Its Influence on Exclusive Breastfeeding Success in Indonesian Infants: A Systematic Literature Review - Septi Aruani; Diniati Sukmana; Qorinah Estiningtyas Sakilah Adnani; Hadi Susiarno; Viktor Abiola Adepoju (Jurnal Bidan Cerdas, 2025)
Background: Exclusive breastfeeding involves providing only breast milk to infants from birth to six months. Globally, 48% of infants were exclusively breastfed in 2023, with Indonesia reporting 68.6% for infants aged 0-5 months. The husband's support plays a crucial role in exclusive breastfeeding success through emotional, informational, instrumental, and evaluative support which enhance maternal comfort and extend breastfeeding duration. This study investigates the impact of spousal support on exclusive breastfeeding for infants (0–6 months). Methods: A literature review was conducted with twenty articles sourced from Google Scholar, Semantic Scholar, and Garuda databases. Results: The review identified that affective support, such as empathy, motivation, and encouragement, was reported in 75% of studies and strongly correlated with maternal confidence and reduced breastfeeding fatigue. Informational support such as guidance on latching techniques or resolving milk supply issues, was present in 50% of studies and was particularly impactful for primiparous mothers. Instrumental support, found in 70% of studies, included household assistance and infant care and was associated with reduced maternal stress and sustained breastfeeding. Appraisal support was also noted but less frequently emphasized. Conclusion: Emotional, informational, and instrumental support from husbands plays a pivotal role in sustaining exclusive breastfeeding. Interventions should prioritize father-inclusive education and engagement strategies to improve breastfeeding outcomes. Policymakers and healthcare providers must actively integrate paternal support components into maternal-child health programs